1992
DOI: 10.1034/j.1399-3054.1992.850110.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of photosynthesis and photosystem II fluorescence in Chlamydomonas reinhardtii after exposure to three levels of high light

Abstract: Falk, S. and Samuelsson, G. 1992. Recovery of photosynthesis and photosystem II fluorescence In Chlamydomonas reinhardtii after exposure to three levels of high light. -Physiol. Plant. 85: 61-68.Recovery from 60 min of photoinhibitory treatment at photosynthetic photon flux densities of 500, 14t)0 and 2200 [imol m"* s^' was followed In cells of the green alga Chlamydomonas reinhardtii grown at 125 [imol m"-s^^. These light treatments represent photoregulation, moderate photoinhibition and strong photoinhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
(21 reference statements)
3
7
0
Order By: Relevance
“…Durin cence quenching, noncyclic electron transport, and photosynthetic light utilization efficiency in C reinhardtii cells inducing the CCM. In several ways, these changes resemble earlier reported changes of the photosynthetic apparatus in C. reinhardtii cells exposed to a mild photoinhibitory treatment (6,7,16). In this context, it is important to emphasize that even though low-Ci cells of C reinhardtii can accumulate CO2 up to 40 times the concentration of an air-equilibrated medium (3), which has a C02(aq) concentration of 10 to 12 Mm, this would still only represent 20 to 30% of the CO2 concentration of a medium in equilibrium with 50 mL L1 C02(g), which has a CO2(aq) concentration of 1600 AM.…”
Section: Low-ci-induced Changes Of Fluorescence Quenchingsupporting
confidence: 75%
See 2 more Smart Citations
“…Durin cence quenching, noncyclic electron transport, and photosynthetic light utilization efficiency in C reinhardtii cells inducing the CCM. In several ways, these changes resemble earlier reported changes of the photosynthetic apparatus in C. reinhardtii cells exposed to a mild photoinhibitory treatment (6,7,16). In this context, it is important to emphasize that even though low-Ci cells of C reinhardtii can accumulate CO2 up to 40 times the concentration of an air-equilibrated medium (3), which has a C02(aq) concentration of 10 to 12 Mm, this would still only represent 20 to 30% of the CO2 concentration of a medium in equilibrium with 50 mL L1 C02(g), which has a CO2(aq) concentration of 1600 AM.…”
Section: Low-ci-induced Changes Of Fluorescence Quenchingsupporting
confidence: 75%
“…For photoinhibited cells of C. reinhardtii, it has previously been shown that a reduced PSII activity is correlated with a decline in the curvature parameter 0 of the photosynthetic light-response curve (6,7,16). Thus, it can be hypothesized that the low 0 observed in C reinhardtii cells with a fully induced CCM (Fig.…”
Section: Low-ci-induced Changes Of Fluorescence Quenchingmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary site of photoinhibition is the reaction centre (D1 protein) of PS II (Demming and Bjorkman, 1987;Jordan, 1996). Photoinhibition is manifested as a decrease in oxygen evolution (Krause, 1988) and photochemical efficiency (Falk and Samuelsson, 1992). The data on the measurement of Fv/Fm during the laboratory incubation of the different samples (Table 10 and 11) show similar kinetics like that off the photosynthetic pigment and protein accumulation and loss and DCPIP photoreduction of both the BGA in control and treated (pesticide) samples.…”
Section: Photosynthetic Efficiencymentioning
confidence: 99%
“…The primary site of photo inhibition is the reaction centre (D1 protein) of PS II (Demming and Bjorkman, 1987). Photo inhibition is manifested as a decrease in oxygen evolution (Krause, 1988) and photochemical efficiency (Falk and Samuelsson, 1992). Photosynthetic functions also have been found to be affected directly or indirectly by heavy metals since thylakoids lamelle of cyanobacterialcells contain all chlorophylls and carotenoids, which are disassembled in the presence of heavy metals (Baszynski and Krupa, 1995;Prasad etal., 2002).…”
Section: Results:-mentioning
confidence: 99%